O impacto do processo educacional da eletrobrás sobre as dimensões do desempenho organizacional - Sousa, Eduardo Bezerra de (2000)
The future will belong to companies that can fully explore process centering. Total Quality program and other initiatives bound to give new shape to organisations have already transformed the work to be done in companies. Now it is time to transform people that work in tem, as to have teams capable of superior performance. In general, the subjects related to human resources are the responsability of the human resourse function. This is the very part of the Eletrobrás that needs to face the most dificult part of the modernization challenge. It seems, however, that the conventional weapons and accumulated expirience of HR people may not be enough to settle the questiono This dissertation suggests that it will be necessary to break up the past, to leave some old concepts and experiences behind and to propose new creative solutions to give companies of the future, the human resources they will need.